Antiparasitic and cytotoxic effect of benznidazole and new metronidazole/eugenol hybrids on Trypanosoma cruzi-induced infection in vitro and in vivo - Santos, Elda Gonçalves Dos (2023)
Despite being discovered more than a century ago, the scarcity of drugs and the side effects of available therapies are among the greatest challenges for the Chagas disease treatment. Our primary investigation was through a detailed critical review of the evidence to assess benznidazole relevance and applicability indifferent stages of the disease. Our findings demonstrated that benznidazole exhibits high bioavailability after oral administration in adults and children; however, the recommended dosage and duration of treatment are often dissociated from pharmacodinamic findings. In addition, the multiple analytical methods used in long-term post-therapeutic follow-up support the evidence that the greatest therapeutic efficacy is obtained when benznidazole-based treatment is administered in acute infections, gradually worsening as the infection becomes chronic. In the face of confirmed therapeutic failure, treatment with benznidazole does not always guarantee a better prognosis, and the patient may develop Chagas Cardiomyopathy as well as untreated patients. Based on these observations, indicating the need for new strategies for Chagas disease treatment, our secondary approach evaluated antiparasitic relevance of two new metronidazole/eugenol molecular hybrids on T. cruzi infection in vitro and in vivo. Our findings showed that the hybrids have a direct antiparasitic effect on T. cruzi, attenuating cellular parasitism, reactive species biosynthesis and oxidative stress in T. cruzi-chalenged cardiomyocytes in vitro. In addition, the hybrids were well tolerated in T. cruzi-infected mice, not being related to mortality or hepatotoxicity. These new molecules also induced a relevant antiparasitic effect by attenuating parasitemia and myocarditis in vivo. In view of the results, one of the hybrids, called AD07 (metronidazole/dihydroeugenol hybrid nitrated at ortho position to hydroxyl), stood out as a potentially relevant candidate for the development of new, safer and more effective drug regimens for the treatment of T. cruzi infection.